The influence of industry sponsorship on the reporting of subgroup analyses within phase III randomised controlled trials in gastrointestinal oncology. Issue 18 (December 2015) - Barton, Sarah; Peckitt, Clare; Sclafani, Francesco; Cunningham, David; Chau, Ian
Abstract: Purpose: Correct interpretation of subgroup analyses (SGA) is important as it influences selection of therapeutic interventions for patient subsets. The primary aim of our study was to compare reporting of SGA between industry and non-industry sponsored trials. Methods: We performed a systematic literature review and extracted data from journal articles (JA) and conference abstracts (CA) published over a decade reporting SGA results of phase III randomised controlled gastrointestinal (GI) oncology trials with patient participants of ≥150. Results: In JA, SGA was reported in 100/145 (69%) trials: 41/54 industry sponsored (76%; 95% confidence interval [CI]: 63–86%) and 59/91 non-industry sponsored (65%; 95% CI: 55–74%) trials (p = 0.16). In CA, SGA was reported in 86/204 (42%) trials: 43/83 industry sponsored (52%; 95% CI: 41–62%) and 43/121 non-industry sponsored (36%; 95% CI: 28–44%) trials (p = 0.02). Number of SGA performed per trial was significantly larger for industry compared to non-industry sponsored trials in both JA (median 6 versus 2, p = 0.003) and CA (median 1 versus 0, p = 0.023). Claims of subgroup effect were made in 52% of trials in JA and 50% in CA, with significant test of interaction evident in only 25% of JA and 16% of CA, with no difference between industry and non-industry trials. Industry sponsored trials with a significant primary end-point reported more SGA (p < 0.001 JA; p = 0.046 CA). Conclusions: Industry sponsored trials reported more SGA. Claimed subgroup effects were often not accompanied by significant interaction test; thus circumspection should be adopted when using SGA to deviate from standard therapeutic decision-making in GI oncology. Highlights: Systematic review was performed on publications of phase III GI oncology RCT subgroup analyses over a decade. Industry sponsored trials reported more subgroup analyses. Claimed subgroup effects are not often accompanied by significant interaction tests. Care should be taken to deviate standard therapeutic decision-making based on subgroup analyses.